Proposal of a content analysis method for advertising that use works of art as a persuasive resource (2019)
Art and advertising, despite their different purposes, are sharing the framework in the advertising that use works of art as a persuasive resource. The use of these artworks supposes a reflection (with a view to the impact and understanding of the target audience) of the publicist, on the way of use of that painting. Graphic design is like an intermediary and responsible for taking the most of work of art to maximize the benefits in the advertising and the brand. It is necessary the development of a Method of Analysis, in order to search a possible relationship with consumer interpretation.